Display Of Cultural Objects Collection At Kotagede Museum Intro Living Museum - Kanisa Triyundari Arselant; Mikke Susanto; Dian Ajeng Kirana (TUMATA: Journal of Arts and Cultural Management, 2023)
Kotagede Intro Living Museum is a museum with local nuances inaugurated in 2021. The museum has three categories of collection assets and is divisible into four space clusters. Each space is notable by theme based on type and collection information. Thus, many people can now access and enjoy buildings used only to store cultural objects. This study aims to discover things related to the display pattern of the cultural objects collection at Kotagede Museum. The research method used is qualitative with a museum display theory approach. Non-participatory direct observation methods, semistructured interviews and literature studies collected data. The results of the study revealed matters related to the display of museum collections, including supporting elements and aspects arranged in the form of type of space, spacefloor design, work material, storyline, exhibition text and labeling of works, visitor circulation, air circulation, lighting and supporting facilities and visual elements.Based on the study's results, it can conclude that the collection display at Kotagede Museum uses rules for the use of cultural heritage buildings. This consideration of building intervention and space adaptation is applied to present the collection.